Discovery of schizophrenia drug targets from DISC1 mechanisms - Kamiya, Atsushi (Henry Stewart Talks, 2013)
Discovery of DISC1, Potential Therapeutics strategies based on the structure and motif of DISC1 protein, DISC1-associated pathways as drug targets, Molecular complexities of DISC1